Effect of cycling cadence on subsequent 3 km running performance in well trained triathletes. Issue 2 (1st April 2003) - Bernard, T; Vercruyssen, F; Grego, F; Hausswirth, C; Lepers, R; Vallier, J-M; Brisswalter, J
Abstract : Objectives: To investigate the effect of three cycling cadences on a subsequent 3000 m track running performance in well trained triathletes. Methods: Nine triathletes completed a maximal cycling test, three cycle-run succession sessions (20 minutes of cycling + a 3000 m run) in random order, and one isolated run (3000 m). During the cycling bout of the cycle-run sessions, subjects had to maintain for 20 minutes one of the three cycling cadences corresponding to 60, 80, and 100 rpm. The metabolic intensity during these cycling bouts corresponded approximately to the cycling competition intensity of our subjects during a sprint triathlon (> 80% V̇o 2 max). Results: A significant effect of the prior cycling exercise was found on middle distance running performance without any cadence effect (625.7 (40.1), 630.0 (44.8), 637.7 (57.9), and 583.0 (28.3) seconds for the 60 rpm run, 80 rpm run, 100 rpm run, and isolated run respectively). However, during the first 500 m of the run, stride rate and running velocity were significantly higher after cycling at 80 or 100 rpm than at 60 rpm (p<0.05). Furthermore, the choice of 60 rpm was associated with a higher fraction of V̇o 2 max sustained during running compared with the other conditions (p<0.05). Conclusions: The results confirm the alteration in running performance completed after the cycling event compared with the isolated run. However, no significant effect of the cadence was observed within the range usually used by triathletes.